The reactions of Latin American and Caribbean governments to the international crisis : an overview of policy measures up to 20 February 2009 - Bello, Omar...[et al.] (ECLAC [Santiago]CL, 2009)
Provides an overview of the measures that have been implemented or announced in the countries of Latin America and the Caribbean. Includes the following categories of measures in monetary and financial policy; fiscal policy and exchange-rate and external trade policy; sectoral policies; and labour and social policies.